Continuing to Become Other: Responding to the Complexities of the Shifting Subject in Qualitative Research Through a Narrative Therapy Lens - Penwarden, Sarah (Qualitative report, 2024)
According to anthropologist Bruner (1987), “stories may have endings, but stories are never over” (p. 17). This notion, of people continuing to tell and retell their life stories to craft preferred ways of living, is a key concept within narrative therapy (Denborough, 2014). However, this concept of the subject whose stories change over time is, at face value, a challenge to the validity of qualitative research data which is seen as enduring over time. Bearing in mind St. Pierre’s (2021) call to continue to reinvent qualitative research in line with the poststructuralist moment, I consider what it might offer qualitative research to view a participant not as static and fixed, but as unfinalized across time. In this regard, I utilize narrative therapy’s view of a person as shifting over time (Combs & Freedman, 2016). I propose three sets of implications for a fluid view of a person for qualitative research: methodological implications in viewing interviews as a slice of life, or as part of longitudinal stories; implications for a researcher in how they relate to their limited knowledge claims with epistemic humility; and practice innovations to invite participants to acknowledge their own unfinalizability and potential to change over time. These implications invite a researcher to ally with the implicitly therapeutic possibilities of qualitative research, which not only describe what is, but opens potential to know what may be.